2009
DOI: 10.1111/j.1540-627x.2009.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Innovation among Spanish Manufacturing SMEs

Abstract: Innovation is widely recognized as a key factor in the competitiveness of nations and firms. Small firms that do not embrace innovation within their core business strategy run the risk of becoming uncompetitive because of obsolete products and processes. Innovative firms are a perquisite for a dynamic and competitive economy.This paper reports on the results of a study that examined barriers to firm innovation among a sample of 294 managers of small and medium-sized enterprises (SMEs) in Spain. The study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
342
1
49

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(452 citation statements)
references
References 63 publications
20
342
1
49
Order By: Relevance
“…Hadjimanolis (1999), in a study of SMEs in Cyprus, showed that the most important internal barriers were the lack of time, inadequacy of R&D activities, design and testing within the company, and inadequate financial resources, while the most challenging external barriers were ease of copying the innovation, government bureaucracy, lack of government support, lack of qualified human resources, government policies, and bank lending. Madrid-Guijarro et al (2009) found that the barriers to innovation that Spanish SMEs faced were the external environment, human resources, and financial position. Mohnen and Rosa (2001), Hyytinen and Toivanen (2005), and Iammarino et al (2009) found that small firms faced significant financial barriers to innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hadjimanolis (1999), in a study of SMEs in Cyprus, showed that the most important internal barriers were the lack of time, inadequacy of R&D activities, design and testing within the company, and inadequate financial resources, while the most challenging external barriers were ease of copying the innovation, government bureaucracy, lack of government support, lack of qualified human resources, government policies, and bank lending. Madrid-Guijarro et al (2009) found that the barriers to innovation that Spanish SMEs faced were the external environment, human resources, and financial position. Mohnen and Rosa (2001), Hyytinen and Toivanen (2005), and Iammarino et al (2009) found that small firms faced significant financial barriers to innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, while financial resources are necessary to carry out innovation activities, there are other factors that may significantly hinder innovation that are related to knowledge, market, and the policy and regulatory environment. These factors are categorized as internal and external and can be revealed and deterring barriers (Stanislawsky and Olczak, 2010;Madrid-Guijarro, Garcia, and Van Auken, 2009;Hadjimanolis, 2003;D'Este et al, 2008;Blanchard et al, 2013;Pellegrino and Savona, 2013;Piatier, 1984). Internal barriers emerge and create resistance within the firm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When we test the null hypothesis, H3, for environmental barriers, we also confirm that "high cost of innovation" and "lack of appropriate source of finance" are two other statistically significant variables, which have a significant impact on the propensity of entrepreneur's innovation decision. Entrepreneurs who consider the innovation costs to be excessive have a smaller propensity for innovating in their decisions (Silva and Leitão, 2007;Tourigny and Le, 2004;Segarra-Blasco et al, 2008;Madrid-Guijarro et al, 2009). Finally, the results of the model show that "lack of qualified personnel" like Segarra-Blasco et al, 2008;Piatier, 1984;Ylinenpää, 1998;Silva et al;2007;Rush and Bessant, 1992;Hadjimanolis, 1999;andRammer et al (2005, 2006), have a significant effect in the propensity to innovate.…”
Section: Variables and Estimation Of Modelmentioning
confidence: 96%
“…La recherche sur la stratégie et le management des organisations s'intéresse depuis longtemps à l'innovation, mais elle a pris encore plus de vigueur au cours des vingt dernières années (Zhang, Macpherson et Jones, 2006 ;Bierly et Daly, 2007 ;Madrid-Guijarro, Garcia et Van Auken, 2009). Il en va de même pour les chercheurs s'intéressant à la performance des PME qui sont, eux aussi, de plus en plus nombreux à se pencher sur les contextes, sur les facteurs, de même que sur les pratiques favorisant l'innovation dans les petites et moyennes entreprises (Claveau, Perez et Prim-Allaz, 2013).…”
Section: La Créativité : Grande Oubliée Des Chercheurs En Innovationunclassified